2022
DOI: 10.5515/kjkiees.2022.33.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Wide-Band Intermediate Frequency Receiver to Minimize the Second Harmonic Signal

Abstract: In this study, an eight-channel wide-band intermediate frequency (IF) receiver with an S-band input frequency, an output frequency of 200 MHz, and a signal bandwidth of 160 MHz was developed. The performance measurement results of the IF receiver showed that the fundamental signal and the second harmonic signal were involved in the bandwidth of the IF receiver output. This was caused by the nonlinearity characteristics of the final stage amplifier. Therefore, the final stage amplifier was changed to a differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…However, over cycles, the oxidation curve for c-Li 15 Si 4 slowly decreased, and a new curve appeared around 0.3 V, which seems to show that the Li 15 Si 4 crystalline phase is diminished by the reduction of silicon reaction level and of silicon electrode capacity. 13,14,21 This research identified that, over each cycle, the curves at the 0.45 V section are reduced, and the curves at the 0.3 V section increase. This research identified that the capacity of the 873 K sample (Fig.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…However, over cycles, the oxidation curve for c-Li 15 Si 4 slowly decreased, and a new curve appeared around 0.3 V, which seems to show that the Li 15 Si 4 crystalline phase is diminished by the reduction of silicon reaction level and of silicon electrode capacity. 13,14,21 This research identified that, over each cycle, the curves at the 0.45 V section are reduced, and the curves at the 0.3 V section increase. This research identified that the capacity of the 873 K sample (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Thus, we can expect a good effect in improving the cycle life of LIB. 14,15 Debye-Scherrer Eq. 1 is to determine the average grain size through XRD peak analysis: 16…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations